2021
DOI: 10.3389/fvets.2020.595149
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Usage Factors and Resistance Profiles of Shiga Toxin-Producing Escherichia coli in Backyard Production Systems From Central Chile

Abstract: Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen and important cause of foodborne disease worldwide. Many animal species in backyard production systems (BPS) harbor STEC, systems characterized by low biosecurity and technification. No information is reported on STEC circulation, antimicrobial resistance (AMR) and potential drivers of antimicrobial usage in Chilean BPS, increasing the risk of maintenance and transmission of zoonotic pathogens and AMR generation. Thus, the aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 107 publications
1
11
0
Order By: Relevance
“…The preponderance of stx 1 isolates recovered from small ruminant animals has also been recorded in other epidemiological studies [11,15,[48][49][50]. This high proportion of stx 1 -positive isolates could be as a result of these isolates being better adapted to colonization of small ruminants than stx 2 or stx 1+2 -positive isolates.…”
Section: Plos Onesupporting
confidence: 68%
See 1 more Smart Citation
“…The preponderance of stx 1 isolates recovered from small ruminant animals has also been recorded in other epidemiological studies [11,15,[48][49][50]. This high proportion of stx 1 -positive isolates could be as a result of these isolates being better adapted to colonization of small ruminants than stx 2 or stx 1+2 -positive isolates.…”
Section: Plos Onesupporting
confidence: 68%
“…Studies which have successfully identified O157 serogroup in sheep or goat feces report a prevalence of between 1.8-11.7% [25,[52][53][54][55]. Pavez-Munoz et al (2021) also failed to recover any O157 isolates from sheep samples collected as part of a backyard production system surveillance [49]. The absence or low prevalence of O157 STEC from sheep and goat feces indicates that sheep and goats may be an unlikely source of human O157 infection.…”
Section: Plos Onementioning
confidence: 99%
“…Twenty-one STEC strains isolated from cattle were sequenced in this study, of which twenty were isolated in 2018 from cattle at abattoirs in the Región Metropolitana of Chile [8], and one was isolated in 2019 from cattle raised in a backyard production system in the same region [49]. Genomic DNA of these 21 STEC strains was extracted using the Wizard Genomic DNA purification kit (Promega, Madison, WI, USA), following the manufacturer's instructions.…”
Section: Bacterial Isolates and Whole-genome Sequencing (Wgs)mentioning
confidence: 99%
“…This fact may be an indirect indicator of a possible underestimation or overestimation of immunity levels for certain diseases [72,73]. The consequences of these practices could have an impact on public and animal health, mainly associated with the generation of antimicrobial resistance against widely used drugs [34,35,48,71,74,75]. Previous studies have detected multidrug resistance in non-typhoidal Salmonella strains from Chilean BPS [76] and sensitivity to a wide range of antimicrobials in STEC isolates from backyard animals [75].…”
Section: Bps Management Characterizationmentioning
confidence: 99%